Efficacy of topical plai (Zingiber Cassumunar) cream extract for symptomatic relief of delayed onset muscle soreness - Klaphajone, Jakkrit; Chutarattana, Natkul; Lee, Pattana (Biomedical Sciences and Clinical Medicine, 2017)
Objective To evaluate the efficacy of topical application of plai cream for symptomatic relief of delayed onset muscle soreness. Study design An experimental double-blind randomized controlled trial of a novel method of symptom relief from delayed onset muscle soreness (DOMS). Setting Suandok Fitness Center, Faculty of Medicine, Chiang Mai University Methods Strenuous biceps curl exercise was used to induce DOMS in the biceps of the non-dominant arm of 30 healthy subjects. The DOMS symptoms appeared within 24 hours following exercise. The subjects were then randomly divided into 2 groups: an experimental (plai) group and a control (placebo) group. All subjects in each group were given a tube of cream to apply to their affected arms. The subjects in the experimental group were given plai cream while the subjects in the control group were given a plai-scented placebo cream with no anti-in fl ammatory ingredients. Pain measurements were made by blinded assessors using the Numeric Rating Scale (NRS) for clinical pain and the Pressure Pain Threshold (PPT) immediately after exercise, at 24-hours after exercise (when fi rst use of the cream was prescribed), and at 72-hours after exercise. Results Both the experimental and the control group showed a signi fi cant decrease in NRS compared to baseline. However, the experimental group had a signi fi cantly greater NRS reduction compared to the control group (3.73±1.53 vs 2.13±1.92, p=0.027). In addition, signi fi cant increases in PPT were observed in the experimental group, whereas no signi fi cant change in PPT was observed in the control group. Conclusions The results indicated that plai cream might be superior to placebo cream for symptomatic relief from DOMS. <br style="font-style: normal; font-variant: normal; font-weight: normal; letter-spacing: normal; line-height: normal; orphans: 2; text-align: -webkit-auto; text-indent: 0px; text-transform: none; white-space: normal; widows: 2; word-spacing: 0px; -webkit-text-size-adjust: auto; -webkit-text-stroke-width: 0px;" />